Muscarinic Receptors Are Responsible for the Cholinergic Modulation of Projection Neurons in the Song Production Brain Nucleus RA of Zebra Finches - Meng, Wei; Wang, Songhua; Yao, Lihua; Zhang, Nan; Li, Dongfeng (Frontiers in Cellular Neuroscience, 2017)
Songbirds are a useful model for the study of learned vocal behavior in vertebrates. The robust nucleus of the arcopallium (RA) is a premotor nucleus in the vocal motor pathway. It receives excitatory synaptic inputs from the anterior forebrain pathway. RA also receives cholinergic inputs from the ventral paleostriatum of the basal forebrain. Our previous study showed that carbachol, a nonselective cholinergic receptor agonist, modulates the electrophysiology of RA projection neurons (PNs), indicating that cholinergic modulation of RA may play an important role in song production. However, the receptor mechanisms underlying these effects are poorly understood. In the present study, we investigated the electrophysiological properties of two acetylcholine receptors on the RA PNs of adult male zebra finches using in vitro whole-cell current clamp. Our results demonstrate that activation of muscarinic acetylcholine receptors (mAChRs) simulate the effects of carbachol. Both carbachol and the mAChR agonist muscarine produced a decrease in the excitability of RA PNs and a hyperpolarization of the membrane potential. The mAChR antagonist atropine blocked the effects of carbachol. Activation of nicotinic acetylcholine receptors (nAChRs) with nAChR agonist nicotine or DMPP had no effect on the excitability of RA PNs, and the nAChR antagonist mecamylamine failed to inhibit the effects of carbachol. These results suggest that mAChRs, but not nAChRs, primarily modulate the effects of carbachol on the activity of RA PNs. Collectively, these findings contribute to our understanding of the mechanism of cholinergic modulation in the vocal nuclei of songbirds.